Răspuns :
[(x : 6) + 6] - 6 = 7
(x : 6) + 6 = 7+6
(x : 6) + 6 = 13
x : 6 = 13 - 6
x : 6 = 7
x = 7 x 6
x = 42
Proba:
42 : 6 = 7
7 + 6 = 13
13 - 6 = 7
(x : 6) + 6 = 7+6
(x : 6) + 6 = 13
x : 6 = 13 - 6
x : 6 = 7
x = 7 x 6
x = 42
Proba:
42 : 6 = 7
7 + 6 = 13
13 - 6 = 7
Metoda inversa:
[tex] \ 7+6=13[/tex];
[tex] \ 13-6=7[/tex];
[tex] \ 7*6=42[/tex].
Te-ai gandit la numarul 42.
V:
42:6=7;
7+6=13;
13-6=7.
[tex] \ 7+6=13[/tex];
[tex] \ 13-6=7[/tex];
[tex] \ 7*6=42[/tex].
Te-ai gandit la numarul 42.
V:
42:6=7;
7+6=13;
13-6=7.